Monitoring in Vivo Behaviors of Protein Nanocages via Encapsulating an NIR-II Ag2S Quantum Dot. (2017) - Li, Chunyan; Li, Feng; Zhang, Yejun; Zhang, Wenjing; Zhang, Xian-En; Wang, Qiangbin
Abstract: Introduction: Protein nanocages (PNCs) have been recognized as a promising platform for nanomedicine innovation. Real-time in vivo tracking of PNCs can provide critically important information for the development of PNC-based diagnostics and therapeutics. Here we demonstrate a strategy for monitoring the behaviors of PNCs in vivo by encapsulating a Ag2 S quantum dot (QD) with fluorescence in the second near-infrared window (NIR-II, 1000-1700 nm) inside the PNC, using a simian virus 40 (SV40) PNC (PNCSV40 ) as a model. Methods: The Ag2 S QD was encapsulated into the PNCSV40 through controllable molecular self-assembly. The dynamic migration of Ag2 S@PNCSV40 in living mouse was tracked in real time under an InGaAs-based shortwave infrared imaging system and was further corroborated by ex vivo imaging, inductively coupled plasma mass spectrometry analysis, and macrophage endocytosis assay. Results: Benefitting from the high spatiotemporal resolution and deep tissue penetration of NIR-II fluorescence imaging, the dynamic distribution of the PNCSV40 in living mice was tracked in real time with high fidelity, revealing rapid clearance from bloodstream within 5 min post-intravenous injection and selective accumulation in liver, spleen and bone marrow. Furthermore, adopting the PEGylation strategy, PEGylated PNCSV40 presents remarkably different behaviors in vivo with significantly prolonged blood circulation and much less uptake in the reticuloendothelial system (RES), leading to desirable pharmacokinetics and pharmacodynamics of PNC-based nanomedicines. Discussion: This study represents the first evidence of real-time tracking of the intrinsic behaviors of PNCs in vivo without interference in PNC-host interactions by encapsulating nanoprobes inside, instead of conjugating nanoprobes onto the outer surface of PNCs. The as-described imaging strategy will facilitate the study of interactions between exogenously introduced PNCs and host body, prompting the development of future protein-based drugs, high-efficacy targeted delivery system, sensors, etc.